Na Transport across Frog Skin at Low External Na Concentrations - BIBER, THOMAS U. L. (The Rockefeller University Press, 1966)
Isolated frog skin was bathed with a dilute solution containing 1 mm NaCl on the outside and with normal Ringer’s solution on the inner surface. Net Na flux was determined by simultaneous measurement of unidirectional fluxes with Na(22) and Na(24) and intracellular electrical potentials were examined with microelectrodes. There was a net inward transport of Na under both open-circuit and short-circuit conditions. The short-circuit current was approximately 15% greater than the net Na flux; the discrepancy could be accounted for by a small outward flux of Cl. The electrical potential profile did not differ greatly from that observed in skins bathed on the outside with normal Ringer’s solution. Under open-circuit conditions, there were usually several potential steps and under short-circuit conditions the cells were negative relative to the bathing solutions. Estimates of epithelial Na concentrations utilizing radioactive Na suggested that if all epithelial Na were in a single compartment, an active entry step would be necessary to allow a net inward Na transport. The results could also be explained by a series arrangement of Na compartments without necessarily postulating an active Na entry. The behavior of the potential profile suggested that this latter alternative was more likely.